Tax Saving Strategies Through the Selection of Business Form - Lawalata, Adinda Abigail Stien; Sari, Mutiara Nilam; Tathawura, Ramza; Pahala, Indra; Wahono, Puji (The Future of Education Journal, 2025)
This study aims to analyze tax-saving strategies through the selection of business entity forms in Indonesia. The analysis focuses on four types of entities: Limited Liability Company (PT), Limited Partnership (CV), cooperative, and foundation, each of which has distinct tax treatments and legal structures. The method used is qualitative descriptive with a literature review approach, utilizing relevant sources published between 2020 and 2025. The results show that choosing the appropriate business entity form can serve as an effective, legal, and sustainable tax planning strategy. A PT offers legal certainty but comes with higher tax and administrative burdens. A CV is more flexible and suitable for MSMEs, benefiting from a lighter final tax rate. Cooperatives receive fiscal incentives on retained earnings (SHU), while foundations have potential tax exemptions for social activities. Therefore, the selection of a business entity should take into account legal aspects, fiscal considerations, and long-term operational goals.